Efficacy of online nutrition professional development for Early Childhood Education Care staff. (30th September 2020) - Wallace, R; Lo, J; Sambell, R; Devine, A
Abstract: Background: Early Childhood Education & Care (ECEC) services are a public health setting that influences the lifelong eating habits and health of young Australians. Over 1.3 million children attend ECEC for 30 hours/week. Overweight/obesity, a risk factor for chronic disease, has been associated with this setting. Research reports sub-optimal food provision, poor role modelling and a lack of nutrition training and confidence. Online nutrition education training was provided to ECEC staff, aiming to increase nutrition knowledge/confidence. Methods: Training was evidence-based, informed by stakeholders and developed by tertiary nutrition experts. ECEC staff were recruited and randomised to intervention or control groups. The intervention group completed an online short course about whole-service approach to healthy eating of 2-3 hours duration. Nutrition knowledge/confidence were measured pre/post-intervention via a pre-validated, online survey. GLM was used to determine differences within and between groups adjusting for years of experience. Results: Participants (n = 116) were mostly female, aged >36 years, with >10 years industry experience. Post-course, compared to the control group, intervention participants significantly increased confidence to offer 2 serves of grains/day and unsweetened cereals, a variety of vegetables and low-sodium foods, and solid fats were avoided. Confidence to avoid serving discretionary foods did not change and cakes/biscuits were offered frequently. Conclusions: Following course completion, intervention participants demonstrated increased confidence to serve foods from core food groups, but both groups reported offering discretionary foods frequently. Some results are promising and may improve the nutritional value of food offered at ECEC, but it appears discretionary foods continue to be overprovided. Further research is required to identify the depth of training required to embed important nutrition education concepts in ECEC settings. Key messages: Evidence-based nutrition education adopting a whole-service approach is effective in increasing ECEC staff nutrition knowledge and confidence to provide foods from core food groups. Further research is required to establish the level of nutrition education appropriate for ECEC staff to avoid the continuing overprovision of discretionary foods to young children.